Theoretical Study on Electronic Structure and Optical Performance of Nickel and Nitrogen Codoped Rutile Titanium Dioxide - Fei Wang; Lei Feng; Dongmei Zhang; Qingguo Tang; Jinsheng Liang; Dan Feng (International Journal of Photoenergy)
The nickel doped, nitrogen doped and nickel + nitrogen codoped rutile titanium dioxide have been investigated by ab initio calculations based on density functional theory. The electronic structure and optical performance of different ions doping models are researched through the obtained results, which reflects that the band gap of nickel and nitrogen codoped system declines apparently; the decrease of electron-hole pairs separation and charge carriers recombination rate becomes more desirable. Moreover, the optical absorption curves of nitrogen and nickel codoped rutile titanium dioxide demonstrate the higher photoresponse for visible-light than that of nickel or nitrogen single doped. The above results could provide theoretical basis for further developing of titanium dioxide photocatalyst and related experimental studies.